From Tradition to Transformation: The Shift of the Mato System in Padang Restaurants from an Islamic Economic Perspective - Miftahul Jannah; Rizal Fahlefi; Ahmad Lutfi (ITQAN: Journal of Islamic Economics, Management, and Finance, 2026)
This study examines the transformation of the traditional mato revenue-sharing system in Padang restaurants into a fixed-wage model within the framework of Islamic economics. Employing a qualitative intrinsic case study design, the research was conducted at a Padang restaurant in West Sumatra that has implemented a wage-based system since its establishment in 2011, despite the owner’s cultural familiarity with mato as a Minangkabau heritage practice. Data were collected through in-depth interviews with the business owner and were analysed thematically using the Miles and Huberman method. The findings indicate that abandoning the mato system does not reflect a rejection of Islamic economic principles, but rather an adaptation to microeconomic dynamics, income instability, and operational efficiency. Islamic ethical values such as ‘adl (justice), amānah (responsibility), riḍā (mutual consent), and ta‘āwun (cooperation) continue to shape wage management and employer–employee relationships. The shift from kinship-based labour to a formal professional structure has generated notable sociocultural implications. Familial values that traditionally functioned as moral safeguards have been reconstructed through transparent administration and structured supervision, without diminishing the spirit of ukhuwah and the ethical foundations of Islamic law. The study concludes that the implementation of Islamic economics should not be judged solely by the structural format of labor systems, but by the internalization of Islamic moral values in business practices. In this regard, Padang Restaurant X represents a model of “Islamic moral economy” rooted in Minangkabau local wisdom.